Methodology of Application of Innovative Educational Technologies from Astronomy to Laboratory Activities - Sayfullaeva, G. I.; Sattorov, A. R. (European Journal of Life Safety and Stability (2660-9630), 2021)
Innovation in Uzbekistan was one of the first to enter the education system after independence as follows: The Legislative Chamber on Innovative Activities for the Development of the Education System was adopted on April 7, 2020, approved by the Senate on June 19, 2020, and is widely used today. This Law, the Law “On Science and Scientific Activity” is aimed at ensuring freedom of scientific creation and information.